The impact of intangibles on value creation: Comparative analysis of the Gu and Lev methodology for the United States software and hardware sector - Leonardo Fernando Cruz Basso; Juliana Albuquerquer Saliba de Oliveira; Herbert Kimura; Erica Sumoyama Braune (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
The aim of this paper was to analyze the contribution of intangible assets in the value creation of companies, using the methodology proposed by Gu and Lev, 2003, Gu and Lev, 2011. The database used was collected in Datastream with information covering the period from 2001 to 2010. The main results indicate that: (i) the variables RD and SGA and RD, SGA and CAPEX represent intangibility proxies for the software and hardware sector, respectively; (ii) comprehensive value explains the market value for the two sectors; and (iii) the intangibility indices ICBV and RI and MtCV, ICM and RI present a positive and significant relationship with shareholder return for the software and hardware sector, respectively. The principal implication of the paper is having found a positive and significant relationship between comprehensive value and market value. Accordingly, if this variable really explains the market value, it is a solution to a problem that afflicts accountants, which is how to account for intangibles in the balance sheet.
Keywords: G20; 330; Intangible assets; Value creation; Total shareholder return